STUDI EKSPLORATIF MOTIVASI BERWIRAUSAHA SKALA MIKRO SEKTOR JASA MAKANAN DI SURABAYA - Serli Wijaya; Tessa L.L Winargo (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2016)
AbstractThe number of micro and SMEs in Surabaya has been growing significantly during the past few years. The purpose of this study was to explore the underlying factors influencing the entrepreneurial motivation amongst those who operate their micro-scale business in the food service sector in Surabaya. Adopting push and pull motivation construct, the questionnaire containing motivational questions was developed. The data was collected from a survey to 100 participants who have operated their businesses located in various traditional culinary centres in Surabaya. Overall, the result revealed eight new factors influencing entrepreneurial motivation. Respondent dissatisfaction with previous job was the only push factors while the other seven factors, namely: 1) economical drive; 2) self-efficacy; 3) self-esteem; 4) social responsibility; 5) freedom to manage business; 6) passion for the job; and 7) look up at role models; were found as the pull motivational factors.Keywords: entrepreneurial motivation, micro-scale entreprises, push-pull motivation, foodservice